Rapid fabrication of complex nanostructures using room-temperature ultrasonic nanoimprinting - Junyu Ge (Nature Portfolio, 2021)
Nanoimprinting faces challenges with imprinting hard materials at low or room temperature, and with fabricating complex nanostructures rapidly. Here, the authors overcome these challenges by a room-temperature ultrasonic nanoimprinting technique that capitalizes on the concentration of ultrasonic energy flow at nanoscale.